Impact Of Leadership, Decision Making, And Job Satisfaction On Performance At Pt Pln (Persero) Uid S2Jb - Ardhika, Ryan; Abdilah, Willy; Santi, Fitri (The Manager Review, 2023)
This study aims to analyze the influence of leadership, decision-making, and job satisfaction on employee performance at PT PLN (PERSERO) UID S2JB. The type of research used is quantitative. In this study, the hypothesis was tested using regression analysis. Our regression results show that: (1) leadership affects employee performance positively and significantly. (2) decision making affects employee performance positively and significantly. (3) job satisfaction affects employee performance positively and significantly.